Survival Outcomes of Patients With Mediastinal Germ Cell Tumors: Experience of a Cancer Center in South America - Vallejo-Yepes, Camilo; Carvajal-Fierro, Carlos Andrés; Brugés-Maya, Ricardo; Beltrán, Julian; Buitrago, Ricardo; Beltrán-Jimenez, Rafael; Carreño-Dueñas, José Alexander (Frontiers in Oncology, 2022)
Purpose Mediastinal germ cell tumors (GCT) are rare neoplasms associated with poor survival prognosis. Due to their low incidence, limited information is available about this disease in South America. The objective of this study is to report the clinical characteristics and outcomes of patients with mediastinal GCT in a cancer center in Colombia. Materials and Methods We conducted a retrospective analysis of patients with mediastinal GCT treated at the National Cancer Institute at Bogota (Colombia) between 2008 and 2020. Survival curves were presented using the Kaplan–Meier method. Chi-square and Cox proportional hazard model tests were used for data analysis. Results Sixty-one patients were included in the study. Of them, 60 were male and 51 (83.6%) of whom had non-seminomatous germ cell tumors (NSGCT). Twenty-nine patients (47.5%) presented with superior vena cava syndrome, and 18 (29.5%) patients had extrapulmonary metastatic involvement. The three-year overall survival (OS) of NSGCT patients was 26%. The 3-year OS of NSGCT patients who underwent surgical resection of residual mediastinal mass after chemotherapy was 59%. Non-surgical management after first-line chemotherapy was associated with a worse survival prognosis in NSGCT patients (p = 0.002). Ten patients with mediastinal seminomatous germ cell tumors (SCGT) achieved a 3-year OS of 100%. Conclusion Mediastinal NSGCT had poor outcomes. Surgery of the residual mass after first-line chemotherapy seems to improve the outcome of NSGCT patients. Advanced disease at presentation may reflect inadequate access to reference cancer centers in Colombia and potentially explain poor survival outcomes in this cohort. On the other hand, mediastinal SCGT is a biologically different disease; most patients will achieve disease remission and long-term survival with first-line chemotherapy.